THE USE OF AUGMENTED REALITY (AR) AND VIRTUAL REALITY (VR) IN TOURISM MARKETING - Ulusoy, S. (Dulaty University, 2024)
Recent technological advancements have transformed the dynamics of interpersonal interaction and communication, creating novel avenues for engagement between companies and consumers. Virtual Reality (VR) and Augmented Reality (AR) have become pivotal innovations, offering individuals innovative tools to navigate this evolving landscape. The tourism and travel industry has notably embraced these immersive technologies. This study independently aims to explore the applications of AR and VR in tourism marketing, drawing insights from diverse sectors such as hotels, restaurants, applications, and tourism providers in Türkiye and globally. Through a comprehensive literature review, the study elucidates key concepts. Two cases, Dedeman İstanbul Hotel and Marriott International Hotels, were examined using a qualitative research approach focusing on case study analysis. The effectiveness of AR and VR technologies in promoting travel has been evaluated. These selected case studies, analyzed through inductive reasoning, serve to illustrate the varied and impactful use of AR and VR technologies in tourism marketing.
Keywords: 11. Sustainability